The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s40749-017-0026-9
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary rehabilitation and cardiovascular risk in COPD: a systematic review

Abstract: Introduction: Pulmonary Rehabilitation (PR) is an effective intervention in COPD however the value of PR in reducing cardiovascular risk in COPD (measured by aortic pulse wave velocity, aPWV) is unclear and there is no existing systematic review. Objectives: To conduct a systematic review examining whether PR results in alteration of CV risk in COPD (as measured by aPWV). Methods: An electronic systematic search concordant with PRISMA guidelines was conducted. The search was complete to the 27th of May 2017. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Furthermore, the effect of PR on CVD risk is largely unknown. A systematic review of studies investigating arterial stiffness in response to PR or an exercise-training programme in COPD patients only found three eligible studies, with conflicting results [153]; however, there may be subpopulations of patients who benefit from PR with regards to CV risk [153].…”
Section: Muscarinic Antagonistsmentioning
confidence: 99%
“…Furthermore, the effect of PR on CVD risk is largely unknown. A systematic review of studies investigating arterial stiffness in response to PR or an exercise-training programme in COPD patients only found three eligible studies, with conflicting results [153]; however, there may be subpopulations of patients who benefit from PR with regards to CV risk [153].…”
Section: Muscarinic Antagonistsmentioning
confidence: 99%
“…We have recently published a systematic review summarising studies examining the effect of PR on CV risk reduction measured by aPWV in COPD [22]. This identified three papers.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary Rehabilitation (PR), a group exercise and education programme is an evidence-based intervention in COPD to reduce symptoms, improve exercise performance, reduce exacerbations and improve health-status [18–21]. We have previously reviewed the literature on the effect of PR on aortic stiffness in COPD [22]. Whilst the large and well-conducted study by Vanfleteren reported that, on average, there was no influence of PR on arterial stiffness in COPD, the data suggest that arterial stiffness responses to PR were highly heterogeneous such that there may have been sub-groups of patients who did and did not benefit.…”
Section: Introductionmentioning
confidence: 99%
“…The main targets of physical rehabilitation are achieved through timely activity, early start of therapeutic gymnastics and physical therapy in combination with dosed walking. Heart rate and systolic pressure are considered the main indicators of the cardiovascular system condition in clinical rehabilitation (Aldabayan et al 2017).…”
Section: Literature Reviewmentioning
confidence: 99%